Peningkatan Keterampilan Berpikir Kritis Melalui Penerapan Model Pembelajaran Creative Problem Solving Pada Peserta Didik Kelas XI-IPA1 SMA Negeri 2 Masamba - Indrasari, Siti Zulfamia; Harnipa, Harnipa; Kadir, Fitriani; Akfar, Mariani; Rahmat, Dedy (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
The objective of this research is to improve critical thinking skill of students class  XI  Science  1 at  SMA  Negeri  2  Masamba  through  creative  problem solving  learning  model. This  is a class action  research  by subjet of student of  class  XI.  Science  I  at  problem  solving.  Masamba  of  academic  year 2015/2016  whiech  consis  36  students.The  result  is  show  that  (1)  learning activities  of  students  thaught  by  creative  problem  solving  learning  model have  improvie  from  cycle  I  to  cycle  II  (2)  observation  result  of  learning manegement  by  teacher  on  the  cycle  1  and  cycle  II  over  80%  thus  it  is categorized is very good (3) the average (3) the average value of the results of  the  test of  critical  thinking  skills  of  students  has  increased  from  the  first cycle of 72 to 81 in the second cycle, (4) the thoroughness of the individual and  the  traditional  skills  of  critical  thinking  of  students  has  increased  from 62.86% in the first cycle to 88.57 % in the second cycle.